Introduction of ferritin gene into rice and the functional analysis of transgenic plants - XU Xiao-hui; GUO Ze-jian; CHENG Zhi-qiang; LI Jun-ying; LI De-bao (浙江大学学报. 农业与生命科学版)
Ferritin is an iron binding and storage protein. In this study, a pea ferritin (Fer) gene was transferred into rice (Oryza sativa cv Xiushui11, japonica), by Agrobacterium-mediated transformation method. The integration of Fer gene into rice genome was confirmed by PCR and Southern blot techniques. Photosynthetic function of the transgenic plants after paraquat treatment was determined by measurement of the maximal yield of the photochemical reaction (Fv/Fm value). The results indicated that transgenic plants exhibited various degrees of tolerance to free radical toxicity. Accumulation of active oxygen species induced by Magnaporthe grisea inoculation was reduced or delayed in transformants as compared with that in the wild type plants. Moreover, tissue iron content of transformants was significantly increased in the seeds and leaves. These results suggest that the expression of Fer gene have elevated tolerance of rice oxidative damage and increased its iron storage, and might provide a promising approach toward overcoming the problem of iron deficient.